Design and synthesis of novel thiourea metal complexes with controllable antibacterial properties. (6th April 2018) - Rakhshani, Sajjad; Rezvani, Ali Reza; Dušek, Michal; Eigner, Václav
Abstract : A new bidentate O, S donor thiourea ligand (L 1 ), namely N ‐(2‐hydroxyethyl)‐ N ′‐2‐chlorobenzoylthiourea, and its oxazolidine derivative (L 2 ) were synthesized. Derivative L 2 was used for the preparation of Ni(L 2 )2 and Cu(L 2 )2 complexes. The compounds were investigated using X‐ray crystallography and Fourier transform infrared, 1 H NMR and UV–visible spectroscopies. Single‐crystal X‐ray analysis showed strong hydrogen bonding interactions between carbonyl oxygen and N(10) ─ H in the L 1 ligand. In addition, the antibacterial activities of these compounds were evaluated against Gram‐positive and Gram‐negative bacteria, measured using the colony count method. The Cu(L 2 )2 complex exhibited a significant antibacterial activity while the activity of the other compounds was much lower. Finally, the relationship between the structure and antibacterial properties of these compounds was investigated using highest occupied and lowest unoccupied molecular orbital energies calculated by density functional theory method based on the 6‐31G*/LANL2DZ basis set. Abstract : Ligand L 1 cannot coordinate metal ions (Ni(II) and Cu(II)) in a bidentate manner because the hydrogen bond between N(10)‐‐H and carbonyl moiety forces this ligand into monodentate coordination by keeping the carbonyl oxygen in the trans position with respect to sulfur. To eliminate this hydrogen bond, we converted L 1 to its oxazoline derivative L 2 .